The relationship between organizational justice and innovative behavior in China’s digital talents: The moderating effect of flexible work arrangement - Lin Li; Brahim Chekima; Ang Hong Loong (RSIS International, 2025)
In today’s highly competitive global market, innovation is essential for corporate sustainability. In the context of increasing technological restrictions imposed by Western nations, China faces heightened pressure to strengthen its domestic innovation capacity. This study highlights the critical role of organizational justice comprising distributive, procedural, interpersonal, and informational justice in fostering employee innovative behavior. A just organizational environment enhances employees' innovation-related awareness and behavior, thereby contributing to both corporate resilience and national technological advancement. Amid the post-pandemic shift toward flexible work arrangements, many digital nomads are gravitating toward Southeast Asia in pursuit of lower living costs and improved work-life balance, which in turn fosters greater innovation. Drawing upon self-determination theory, this study analyses data from 406 participants and confirms that organizational justice positively influences the innovative behavior of digital talents in China. However, flexible work arrangements are found to only partially moderate this relationship. The findings offer practical implications for policymakers, business leaders, and digital professionals. Promoting organizational justice can serve as a strategic response to technological sanctions and support national self-reliance. In the context of China’s demanding 996 work culture, flexible work arrangements may help alleviate burnout, stimulate innovation, and enhance competitive advantage. For individuals, maintaining autonomy and work life balance is essential for sustaining innovation and achieving long-term career satisfaction, thereby contributing to broader technological progress.